(untitled) (Journal of European Studies (JES), 2017)
For long, Europe has been a migrant destination. It has seen extensive movement within its borders as well as received traffic from other continents. The conflagrations, which took place on the banks of Rhine and Elba, evicted many a people from their ancestral dwellings. They moved in the direction of safer abodes. This study retrospectively explores European disposition toward the refugees while keeping the Syrian turmoil in perspective. The strategic behaviour at the supra national level (European Union) differs starkly from the temper of individual member states. Whereas Brussels strives to uphold the ideals, on which the Union stands, some national governments appear distrustful.